Comparison of postoperative complications of ileal conduits versus orthotopic neobladders - Demaegd, Liesbeth (Transl Androl Urol, 2020)
BACKGROUND: Radical cystectomy (RC) and urinary diversion (UD), with either an ileal conduit (IC) or an orthotopic neobladder (NB), is a complex surgery, in which various complications can occur. In this study, we compared postoperative complication rates after a RC and UD performed for the treatment of muscle-invasive bladder cancer or recurring high-risk non-muscle-invasive bladder cancer in our center. METHODS: We retrospectively included 604 patients that underwent UDs from December 1996 to August 2015. Complications were classified by type and severity according to the Clavien-Dindo classification (CDC). Univariate and multivariate analyses were performed to identify predictive factors of short-term (≤30 d), intermediate-term (31–90 d), and long-term (>90 d) complications. RESULTS: Four hundred and forty-five (74%) and 159 (26%) patients received ICs and NBs, respectively. These groups had significantly different long-term complication rates (IC: 39.7% vs. NB: 49%, P=0.046), but similar short-term (P=0.319) and intermediate-term complication rates (P=0.397). Short-term complications (CDC I–V) were predicted by male gender, age-adjusted Charlson comorbidity index (aCCI) ≥3, and American Society of Anesthesiologists (ASA) score ≥3. Compared to minor short-term complications (CDC I–II), major short-term complications (CDC III–V) were predicted by male gender and a previous abdominal/pelvic surgery, and long-term major complications were predicted by the type of UD (NB). CONCLUSIONS: The increasing risk of short-term complications with increasing aCCI and ASA score can be used when counseling the patients who are planned to undergo a RC with UD. Patients that receive NBs should be informed of the increased risk of reoperations compared to an IC.